A legal study of copyright protection in Malaysia / Sudirman Haji Arshad - Sudirman , Haji Arshad (1979)
The purpose of this paper is to give an objective evaluation of the legal aspects of the Copyright protection afforded by the Copyright Act 1969 of Malaysia. The write shall confine its discussion to the study of substantive law and the main concepts of the Act, as well as infringement of the Copyright, and remedies available thereto. Where necessary, comparisons with the English Copyright Act as well as the International Copyright Convention will be dealt with.